An Investigation on the Clinical Features and Neurochemical Changes in Parkinson's Disease With Depression - Lian, Teng-Hong; Guo, Peng; Zuo, Li-Jun; Hu, Yang; Yu, Shu-Yang; Liu, Li; Jin, Zhao; Yu, Qiu-Jin; Wang, Rui-Dan; Li, Li-Xia; Piao, Ying-Shan; Zhang, Wei (Frontiers in Psychiatry, 2019)
Objective To investigate the clinical features and neurochemical changes in Parkinson’s disease with depression (PD-D). Methods A total of 478 PD patients were divided into PD-D and PD patients without depression (PD-ND) groups according to the 24-item Hamilton Depression Rating Scale (HAMD-24) score. Demographic variables, motor and non-motor symptoms and activities of daily life were evaluated. The independent influencing factors of PD-D were investigated via binary logistic regression analysis. The levels of neurotransmitters in cerebrospinal fluid (CSF) were measured and their correlations with HAMD-24 score were analyzed. Results The proportion of PD-D was 59.0%, of which 76.95%, 20.92% and 2.13% had mild, moderate, and severe depression, respectively. Anxiety/somatization was the most prevalent sub-factor of HAMD-24 in PD-D. The scores of UPDRS III, postural instability gait difficulty (PIGD) type and the scores of 14-item Hamilton Anxiety Scale (HAMA) and 14-item Chalder Fatigue Scale (FS) were independently associated with PD-D. The levels of dopamine (DA) and 5-hydroxytryptamine (5-HT) were all significantly reduced in PD-D group compared with those in PD-ND group. HAMD scores were negatively correlated with the DA levels in CSF. Conclusions PD patients have a high proportion of depression, mainly of mild and moderate levels. The proﬁle of depression in PD population is subtly different from that of the general population. Motor symptoms, PIGD type, anxiety and fatigue are the significant influencing factors of PD-D. Compared to 5-HT, DA may play a more important role in PD-D.